Forest fragmentation in China and its effect on biodiversity. (6th May 2019) - Liu, Jiajia; Coomes, David A.; Gibson, Luke; Hu, Guang; Liu, Jinliang; Luo, Yangqing; Wu, Chuping; Yu, Mingjian
ABSTRACT: Land‐use change is fragmenting natural ecosystems, with major consequences for biodiversity. This paper reviews fragmentation trends – historical and current – in China, the fourth largest country on Earth, and explores its consequences. Remote sensing makes it possible to track land‐use change at a global scale and monitor fragmentation of dwindling natural landscapes. Yet few studies have linked fragmentation mapped remotely with impacts on biodiversity within human‐modified landscapes. Recent reforestation programs have caused substantial increases in forest cover but have not stopped fragmentation, because the new forests are mostly monocultures that further fragment China's remnant old‐growth lowland forests that harbour the highest levels of biodiversity. Fragmentation – and associated biodiversity declines – is unevenly distributed in China's forests, being most problematic where agricultural expansion is occurring in the southwest and northeast, serious in the densely populated eastern regions where urbanisation and transport infrastructure are modifying landscapes, but less of a problem in other regions. Analyses of temporal trends show that the drivers of forest fragmentation are shifting from mainly agricultural expansion to urbanisation and infrastructure development. Most of China's old‐growth forests persist in small, isolated fragments from which many native species have disappeared, on land unsuitable for human utilisation. Fragmentation throughout China is likely to have major consequences on biodiversity conservation, but few studies have considered these large‐scale processes at the national level. Our review fills this research gap and puts forward a systematic perspective relevant to China and beyond.